Unveiling the Dot-Perspective Task: Integrating Implicit-Mentalistic with Sub-Mentalistic Processes - Cong Fan; Tirta Susilo; Jason Low (Psych, 2023)
Adults’ performances on the dot-perspective task showed a consistency effect: participants were slower to judge their own visual perspective when their own perspective and others’ perspective were different compared to when both perspectives were the same. This effect has been explained by two competing accounts: the implicit mentalising account suggests the effect arises from relatively automatic tracking of others’ visual perspectives, whereas the submentalising account suggests the effect arises from domain-general attentional orienting. We conducted three experiments to adjudicate between the two competing accounts. Experiment 1 manipulated eye–head directional cues (gaze-averted-face versus head-averted-face) and measured its effect on implicit mentalising (in the dot-perspective task) and attentional orienting (in the Posner task). Eye–head directional cues modulated attentional orienting but not implicit mentalising, supporting the importance of visual access and the existence of implicit mentalising in the dot-perspective task. Experiment 2 compared the effect of gaze-averted versus finger-pointing agents. Finger-pointing direction might induce attentional orienting effects on both tasks. Experiment 3 combined finger-pointing with manipulation of the agent’s visual access (eyes-sighted versus eyes-covered) on the dot-perspective task. Visual access did not modulate the consistency effect when finger-pointing was simultaneously displayed. The findings of Experiments 2 and 3 indicated the contribution of the sub-mentalistic process to the dot-perspective task. Overall, the findings suggest that implicit mentalising and submentalising may co-exist in human social perceptual processes. Visual access appears to play a dominant role in modulating implicit mentalising on the dot-perspective task, but the process may be interfered with by finger-pointing cues (more salient than gaze cues) via a sub-mentalistic attentional-orienting mechanism.